Biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer blade coating and hot press molding process and preparation method of biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material

Through layer-by-layer scraping and hot-pressing forming technology combined with bionic mineralization and nanocomposite technology, a biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material was prepared, solving the mechanical properties and chemical components of existing materials. The matching problem achieves efficient skull defect regeneration and biodegradable properties.

CN119424756APending Publication Date: 2025-02-14ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411302251.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing skull repair materials do not match natural bones in terms of mechanical properties and chemical components, and are prone to deform or breakage during the growth of children's skulls, making it impossible to effectively achieve high-quality skull defect regeneration.

Method used

Using layer-by-layer scraping and hot-pressing molding, combined with bionic mineralization treatment and nanocomposite technology, biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material is prepared. CNC and HA-CNC fillers are used in the material to simulate human bones. The proportion of organic and inorganic components of the tissue.

Benefits of technology

It achieves high mechanical properties and structural stability, can match various skull defects, promote cell growth and bone function recovery, the material can be biodegradable, avoid secondary surgery and reduce damage to patients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424756A_ABST
    Figure CN119424756A_ABST
Patent Text Reader

Abstract

The invention discloses a biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on a layer-by-layer blade coating and hot press molding process and a preparation method thereof. The preparation method comprises the following steps: 1) forming a hydroxyapatite coating structure (HA-CNC) on the surface of the cellulose nanocrystal by using a biomimetic mineralization method; (2) preparing a mixed solution of PLGA and HA-CNC, performing layer-by-layer blade coating operation on a heating stage, and repeating the blade coating process until the thickness meets the required requirement after the solvent is volatilized; 3) adopting a hot press molding process and secondary shaping to obtain a sample; and (4) after cooling to room temperature, forming a pore structure and an outer side contour conforming to the shape of a skull defect area on the sample obtained in the step (3) by using a cutting process, so as to obtain the HA-CNC composite PLGA porous skull repair scaffold material. After sterilization, the stent material can be implanted into a skull defect area for regeneration and repair. The scaffold material has mechanical properties close to those of natural bones, high HA content and pores, and is beneficial to efficient repair of skull defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation technology of a bone repair material, and in particular to a biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer scraping and hot pressing molding technology and a preparation method thereof. Background Art

[0002] The skull is the last physical protective barrier of the brain. Once it is damaged, the safety of the brain will be seriously threatened. At the same time, skull defects will also affect the patient's appearance. However, with the current development of transportation and industry, the incidence of skull injuries has increased year by year. How to achieve high-quality repair of skull defects has become a major clinical problem that needs to be solved in this field.

[0003] At present, the main clinical treatment methods are to use autologous skull preservation transplantation and artificial skull materials for repair. However, the source of autologous materials is limited, and secondary damage will be caused to the patient during the material collection, increasing the patient's physical and psychological burden; while artificial skull repair materials that have entered clinical use mainly include PEEK, titanium mesh, plexiglass, etc., which are basically in the most basic physical filling stage. As a popular research direction in the field of bone repair, tissue engineering technology has developed a series of repair materials based on hydrogels or scaffolds. Although they have good bone repair activity and degradable properties, these materials often do not have similar chemical composition and mechanical properties to natural bones, and the materials are very fragile during use, especially unable to adapt to the growth process of children's skulls, and are prone to deformation or damage.

[0004] Therefore, in response to the above problems, the present invention selects CNC treated with biomimetic mineralization and PLGA with in vivo biodegradation function as raw materials, and combines layer-by-layer scraping and hot pressing molding processes to prepare a biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material with high mechanical properties, which can meet the needs of skull repair and achieve efficient skull defect regeneration. Summary of the invention

[0005] The purpose of the present invention is to provide a biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material and a preparation method thereof based on layer-by-layer scraping and hot pressing molding process to address the problems of low efficiency of traditional skull defect repair, which can meet the needs of skull repair and achieve efficient skull defect regeneration.

[0006] The present invention is implemented by the following technical solutions:

[0007] A method for preparing a biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer scraping and hot pressing molding process, comprising the following steps:

[0008] 1) Cellulose nanocrystals (CNC) are combined with a surface biomimetic mineralization process to form a hydroxyapatite coating structure on the surface of CNC to obtain HA-CNC nanocomposites;

[0009] 2) preparing HA-CNC / PLGA solution, and performing layer-by-layer scraping on a hot plate until the thickness reaches the standard, thereby obtaining a multi-layered HA-CNC / PLGA preform;

[0010] 3) placing the HA-CNC / PLGA preform in a preheated mold and using a hot pressing process to form a composite polymer film to obtain an initial sample;

[0011] The initial sample is subjected to secondary shaping using a pressure block, and then dialyzed and dried to obtain a sample;

[0012] 4) Using a cutting process, a pore structure and an outer contour that conforms to the shape of the skull defect area are formed on the sample obtained in step 3), thereby obtaining a HA-CNC composite PLGA porous skull repair scaffold material. After sterilization, the scaffold material can be implanted into the skull defect area for regeneration and repair.

[0013] Furthermore, in step 1), during the surface bionic mineralization process, the formula of the bionic mineralization liquid is: sodium chloride 70-100mM, potassium chloride 30-50mM, magnesium sulfate 0.4-0.75mM, magnesium chloride 0.8-1.2mM, calcium chloride 4-6mM, sodium bicarbonate 0.2-0.4mM, calcium dihydrogen phosphate 1.2-1.6mM, dicalcium hydrogen phosphate 0.4-0.6mM, sodium sulfate 0.025-0.05mM, HEPES 15-22mM, the solvent is deionized water, the concentration of CNC is 2.5-10wt%, the magnetic stirring is 20-40r / min, the temperature is 35-37°C, the bionic mineralization time is 3-5 days, and after the bionic mineralization is completed, deionized water is used for centrifugal washing and dried at 50-60°C.

[0014] Furthermore, in step 2), during the preparation of the HA-CNC / PLGA solution, the ratio of PGA to PLA in the PLGA molecule is 25:75 to 75:25, the molecular weight is 10,000-100,000, the concentration of PLGA is 15-25wt%, the solvent is one of N,N-dimethylacetamide, dichloromethane and chloroform, and the dissolution process is heating to 80-90°C and stirring for 2-3h to obtain a PLGA solution; 10-20wt% HA-CNC is added to the PLGA solution, and after stirring, ultrasonic-assisted dispersion is performed for 30-60min, and the solution is allowed to stand for degassing.

[0015] Furthermore, in the layer-by-layer scraping process of step 2), the temperature of the hot stage is 50-60° C., and the HA-CNC / PLGA solution is scraped layer by layer on the hot stage using a scraper. After the solvent of the previous layer evaporates completely, the next scraping cycle is continued. The standard thickness is 6 mm-1.5 cm.

[0016] Furthermore, in step 3), the mold is preheated to 80-120° C., and during the hot pressing process, the hot pressing target temperature is 150-200° C., the pressure is 5-10 MPa, and the time is 30-180 s. After that, the compressive load is removed and the mold is naturally cooled and solidified.

[0017] Furthermore, in step 3), the secondary shaping pressure is 5-6 MPa and the time is 5-10 min;

[0018] During the dialysis process, deionized water was dialyzed for 12-24 hours, and the solution was changed every 2 hours;

[0019] During the drying process, the drying temperature is 50-60°C and the drying time is 5-10h.

[0020] Furthermore, during the cutting process in step 4), an array cutter and a wire saw can be used to form a hole structure array on the sample. The hole structure is a round hole or a square hole with a size of 400-600 μm, and adjacent hole structures are spaced 400-600 μm apart.

[0021] A biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer scraping and hot pressing molding process is obtained by using any of the above-mentioned preparation methods.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] 1) The present invention uses biomimetic mineralization solution, CNC, PLGA, etc. as raw materials, and combines biomimetic mineralization, nanocomposite, layer-by-layer scraping, hot pressing, cutting and other combined processes to prepare a biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer scraping and hot pressing processes. The above raw material selection and process combination are original to the present invention.

[0024] 2) The CNC used in the present invention has a large number of hydroxyl functional groups on its surface, and therefore has very good dispersibility. After the in-situ biomimetic mineralized HA coating is applied to its surface, the dispersibility of HA is indirectly improved, which can provide the possibility of nanocompositing more HA in the PLGA matrix. In the present invention, the concentration of PLGA is 15-25wt%, while the concentration of HA-CNC can reach 10-20wt%, which is closer to the ratio of organic and inorganic components of natural bone tissue in the human body, thereby improving the effect of bone repair.

[0025] 3) The present invention uses a combination of nanocomposite, layer-by-layer scraping and hot pressing processes to simultaneously introduce nanocomposite and multi-layer stacking structures into the PLGA porous skull repair scaffold material, thereby giving the scaffold material high mechanical stability and structural stability. Specifically: the first reinforcement is achieved by nanocompositing a high concentration of HA-CNC filler in a high concentration of PLGA matrix; secondly, by the layer-by-layer scraping process, HA-CNC and PLGA are evenly spread and gradually form a layer-by-layer docking composite structure to achieve the second reinforcement; finally, by the hot pressing process, the pores between the layer-by-layer stacked structures are further compacted, so that the preform forms a complete structural whole, achieving the third reinforcement.

[0026] 4) The biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer scraping and hot pressing molding process in the present invention has matching various skull defects, promoting cell growth, promoting osteogenic function, high mechanical properties, and biodegradability, meeting the needs of skull defect treatment. Among them, wire saw cutting can be performed according to the CT results to obtain the outline of the scaffold material that meets the skull defect wound of different patients; secondly, the porous structure on the scaffold material provides a spatial site for cell growth, which can promote the growth of cells in the pores and accelerate the repair process; the high concentration of HA-CNC filler inside can release calcium ions and phosphate ions through the continuous degradation of HA, thereby inducing cell osteogenic differentiation to achieve the purpose of bone repair; and the scaffold material in the present invention has high mechanical properties, will not easily break and deform during use, will not affect the wound surface and internal brain tissue, and finally the material (PLGA, HA-CNC) will also be biodegraded as the use cycle is extended, no secondary surgery is required to remove it, and no secondary damage will be caused to the patient.

[0027] 5) The sample of the present invention can be cut into a porous structure with a determined pore size to introduce a scaffold material, and at the same time, the outer contour of the scaffold material can be ensured to match the shape of the skull defect area, which can meet the needs of different patients with different skull defect symptoms. The technology is universal and convenient. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the preparation process of the biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer scraping and hot pressing molding process of the present invention;

[0029] Figure 2 This is the in vivo repair MicroCT result of the biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer scraping and hot pressing molding process in an embodiment of the present invention (Figure a corresponds to Example 1, and Figure b corresponds to Example 1). DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further explained below with reference to the accompanying drawings and specific examples.

[0031] Comparative Example 1:

[0032] 1) PLGA (PGA:PLA ratio of 50:50, molecular weight 20000) was dispersed in N,N-dimethylacetamide solvent, stirred and dissolved for 30 minutes, and a high concentration of 15wt% PLGA solution was obtained after standing and degassing, and layer-by-layer scraping operation was performed on a hot stage (the hot stage temperature was 50°C, and the PLGA solution was scraped on the upper layer of the hot stage with a scraper, and the next scraping cycle was continued after the upper layer of the solvent was completely evaporated) until the thickness of the entire coating reached 8mm, thereby obtaining a PLGA preform with a multilayer structure;

[0033] 2) First, the PLGA preform is placed in a mold preheated to 80°C, and after the temperature reaches the target temperature of 180°C, a hot pressing molding process is performed with a pressure of 10 MPa and a time of 60 seconds, and then the compressive load is removed and the preform is naturally cooled and solidified to form a composite polymer film; a pressure block is used to perform secondary shaping with a pressure of 5 MPa and a time of 5 minutes, and the preform is further dialyzed with deionized water for 12 hours (the liquid is changed every 2 hours), and dried at 50°C for 5 hours;

[0034] 3) Using a cutter and a wire saw, a hole structure array (400 μm square holes, 400 μm apart) and an outer contour conforming to the shape of the skull defect area are formed on the sample obtained in step 3) to obtain a PLGA porous skull repair scaffold material. After sterilization, the scaffold material is implanted into a rat skull defect model for regeneration and repair simulation.

[0035] The CCK-8 result of the scaffold material in this comparative example after 7 days of culture with BMSCs was 93.2%, and the compressive strength of the material was 24.3MPa. After 14 days of co-culture with BMSCs, PCR detection was performed, and the expression of osteogenesis-related genes such as Runx2 was not significantly upregulated. After the above material was implanted into the rat skull model and cultured for 28 days, the material was partially degraded, and the Micro-CT results showed that the new bone regeneration effect was poor. Figure 2 Middle a.

[0036] Embodiment 1:

[0037] 1) 5 wt % CNC was added into a biomimetic mineralization solution (sodium chloride 70 mM, potassium chloride 50 mM, magnesium sulfate 0.5 mM, magnesium chloride 0.8 mM, calcium chloride 6 mM, sodium bicarbonate 0.2 mM, calcium dihydrogen phosphate 1.3 mM, calcium hydrogen phosphate 0.4 mM, sodium sulfate 0.025 mM, HEPES 15 mM, and the solvent was deionized water), and mineralized for 5 days at 37° C. and 30 r / min magnetic stirring conditions to form a hydroxyapatite coating structure on the surface of the cellulose nanocrystals, and the HA-CNC nanocomposite material was obtained after centrifugal washing 5 times with deionized water and drying at 50° C.;

[0038] 2) 15wt% PLGA (PGA to PLA ratio of 50:50, molecular weight 20000) and 10wt% HA-CNC were dispersed in N,N-dimethylacetamide solvent, and ultrasonic-assisted dispersion was performed for 30 minutes after stirring. After standing and degassing, a high-concentration HA-CNC / PLGA solution was obtained, and layer-by-layer scraping operation was performed on a hot stage (the hot stage temperature was 50°C, and the HA-CNC / PLGA solution was scraped on the upper layer of the hot stage with a scraper. After the upper layer of solvent evaporated completely, the next scraping cycle was continued) until the thickness of the entire coating reached 8mm, and a HA-CNC / PLGA preform with a multilayer structure was obtained;

[0039] 3) First, the HA-CNC / PLGA preform is placed in a mold preheated to 80°C, and after the temperature reaches the target temperature of 180°C, a hot pressing molding process is used with a pressure of 10 MPa and a time of 60 seconds, and then the compressive load is removed, and the preform is naturally cooled and solidified to form a composite polymer film; a pressure block is used to perform secondary shaping with a pressure of 5 MPa and a time of 5 minutes, and the preform is further dialyzed with deionized water for 12 hours (the liquid is changed every 2 hours), and dried at 50°C for 5 hours;

[0040] 4) Using a cutter and a wire saw, a hole structure array (400 μm square holes, 400 μm apart) and an outer contour conforming to the shape of the skull defect area are formed on the sample obtained in step 3) to obtain the desired HA-CNC composite PLGA porous skull repair scaffold material. After sterilization, the scaffold material is implanted into a rat skull defect model for regeneration and repair simulation.

[0041] The CCK-8 result of the scaffold material in this example after culturing with BMSCs for 7 days was 88.1%, and the compressive strength of the material was 31.8 MPa. After 14 days of co-culture with BMSCs, PCR detection was performed, and the expression of osteogenic related genes, such as Runx2, was about 376% of that in comparative example 1. After the above material was implanted into a rat skull model and cultured for 28 days, the material was partially degraded, and the Micro-CT results showed that obvious new bone was generated in the holes and edges of the scaffold, such as Figure 2 Middle b.

[0042] Embodiment 2:

[0043] 1) 5 wt % CNC was added into a biomimetic mineralization solution (sodium chloride 70 mM, potassium chloride 50 mM, magnesium sulfate 0.5 mM, magnesium chloride 0.8 mM, calcium chloride 6 mM, sodium bicarbonate 0.2 mM, calcium dihydrogen phosphate 1.3 mM, calcium hydrogen phosphate 0.4 mM, sodium sulfate 0.025 mM, HEPES 15 mM, and the solvent was deionized water), and mineralized for 5 days at 37° C. and 30 r / min magnetic stirring conditions to form a hydroxyapatite coating structure on the surface of the cellulose nanocrystals, and the HA-CNC nanocomposite material was obtained after centrifugal washing 5 times with deionized water and drying at 50° C.;

[0044] 2) 15wt% PLGA (PGA to PLA ratio of 50:50, molecular weight 20000) and 20wt% HA-CNC are dispersed in N,N-dimethylacetamide solvent, stirred and ultrasonically dispersed for 30-60min, and allowed to stand for degassing to obtain a high-concentration HA-CNC / PLGA solution, which is then scraped layer by layer on a hot stage (the hot stage temperature is 50°C, and a scraper is used to scrape the HA-CNC / PLGA solution on the upper layer of the hot stage, and the next scraping cycle is continued after the upper layer of solvent evaporates completely) until the thickness of the entire coating reaches 8mm, thereby obtaining a HA-CNC / PLGA preform with a multilayer structure;

[0045] 3) First, the HA-CNC / PLGA preform is placed in a mold preheated to 80°C, and after the temperature rises to the target temperature of 180°C, a hot pressing molding process is used with a pressure of 10 MPa and a time of 60 seconds, and then the compressive load is removed and the preform is naturally cooled and solidified to form a composite polymer film; a pressure block is used to perform secondary shaping with a pressure of 5 MPa and a time of 5 minutes, and the preform is further dialyzed with deionized water for 12 hours (the liquid is changed every 2 hours), and dried at 50°C for 5 hours;

[0046] 4) Using a cutter and a wire saw, a hole structure array (400 μm square holes, 400 μm apart) and an outer contour conforming to the shape of the skull defect area are formed on the sample obtained in step 3) to obtain the desired HA-CNC composite PLGA porous skull repair scaffold material. After sterilization, the scaffold material is implanted into a rat skull defect model for regeneration and repair simulation.

[0047] Compared with Example 1, this example increases the HA-CNC concentration. The CCK-8 result of the scaffold material in this example after culturing with BMSCs for 7 days was 85.2%, and the compressive strength of the material was 34.6MPa. PCR detection was performed after 14 days of co-culture with BMSCs, and the expression of osteogenesis-related genes, such as Runx2, was about 187% of that in Example 1. After the above-mentioned material was implanted into a rat skull model and cultured for 28 days, the material was partially degraded, and the Micro-CT results showed that obvious new bone was generated in the holes and edges of the scaffold.

[0048] Embodiment 3:

[0049] 1) 5 wt % CNC was added into a biomimetic mineralization solution (sodium chloride 70 mM, potassium chloride 50 mM, magnesium sulfate 0.5 mM, magnesium chloride 0.8 mM, calcium chloride 6 mM, sodium bicarbonate 0.2 mM, calcium dihydrogen phosphate 1.3 mM, calcium hydrogen phosphate 0.4 mM, sodium sulfate 0.025 mM, HEPES 15 mM, and the solvent was deionized water), and mineralized for 5 days at 37° C. and 30 r / min magnetic stirring conditions to form a hydroxyapatite coating structure on the surface of the cellulose nanocrystals, and the HA-CNC nanocomposite material was obtained after centrifugal washing 5 times with deionized water and drying at 50° C.;

[0050] 2) 15wt% PLGA (PGA to PLA ratio of 50:50, molecular weight 20000) and 10wt% HA-CNC were dispersed in N,N-dimethylacetamide solvent, and ultrasonic-assisted dispersion was performed for 30-60min after stirring. After standing and degassing, a high-concentration mixed solution was obtained, and layer-by-layer scraping operation was performed on a hot stage (the hot stage temperature was 50°C, and the HA-CNC / PLGA solution was scraped on the upper layer of the hot stage with a scraper, and the next scraping cycle was continued after the upper layer of the solvent evaporated completely) until the thickness of the entire coating reached 8mm, and a HA-CNC / PLGA preform with a multilayer structure was obtained;

[0051] 3) First, the HA-CNC / PLGA preform is placed in a mold preheated to 80°C, and after the temperature rises to the target temperature of 180°C, a hot pressing molding process is used with a pressure of 10 MPa and a time of 60 seconds, and then the compressive load is removed and the preform is naturally cooled and solidified to form a composite polymer film; a pressure block is used to perform secondary shaping with a pressure of 5 MPa and a time of 5 minutes, and the preform is further dialyzed with deionized water for 12 hours (the liquid is changed every 2 hours), and dried at 50°C for 5 hours;

[0052] 4) The sample obtained in step 3) was processed using a wire saw and cutting process to obtain a HA-CNC composite PLGA skull repair material that conforms to the shape of the skull defect area, without constructing a pore structure array. After sterilization, the above material was implanted into a rat skull defect model for regeneration and repair simulation.

[0053] Compared with Example 1, this example does not construct a pore structure on HA-CNC / PLGA. The CCK-8 result of the material in this example after culturing with BMSCs for 7 days was 89.4%, and the compressive strength of the material was 38.7MPa. PCR detection was performed after 14 days of co-culture with BMSCs, and the expression of osteogenesis-related genes, such as Runx2, was about 87% of that in Example 1. After the above-mentioned material was implanted into a rat skull model and cultured for 28 days, the edge of the material was partially degraded, and the Micro-CT results showed that obvious new bone was generated at the edge of the material.

Claims

1. A method for preparing a biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer scraping and hot pressing molding process, characterized in that: The following steps are involved: 1) Using a surface biomimetic mineralization process to form a hydroxyapatite coating on the CNC surface to obtain a HA-CNC nanocomposite material; 2) preparing a HA-CNC / PLGA solution, standing it for degassing, and performing a layer-by-layer scraping operation on a hot table. After the solvent in the coating evaporates, the scraping process is repeated until the thickness reaches the standard, thereby obtaining a multi-layered HA-CNC / PLGA preform; 3) placing the HA-CNC / PLGA preform in a preheated mold and using a hot pressing process to form a composite polymer film to obtain an initial sample; The initial sample is subjected to secondary shaping using a pressure block, and then dialyzed and dried to obtain a sample; 4) Using a cutting process, a pore structure and an outer contour that conforms to the shape of the skull defect area are formed on the sample obtained in step 3), thereby obtaining a HA-CNC composite PLGA porous skull repair scaffold material.

2. The method for preparing the biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer scraping and hot pressing molding process according to claim 1, characterized in that: The surface bionic mineralization process described in step 1) is specifically as follows: using a bionic mineralization liquid with a formula of: 70-100mM sodium chloride, 30-50mM potassium chloride, 0.4-0.75mM magnesium sulfate, 0.8-1.2mM magnesium chloride, 4-6mM calcium chloride, 0.2-0.4mM sodium bicarbonate, 1.2-1.6mM calcium dihydrogen phosphate, 0.4-0.6mM dicalcium hydrogen phosphate, 0.025-0.05mM sodium sulfate, 15-22mM HEPES, and the solvent is deionized water. CNC is added to the bionic mineralization liquid at a concentration of 2.5-10wt%, with magnetic stirring at 20-40r / min, at a temperature of 35-37°C, and for a bionic mineralization time of 3-5 days. After the bionic mineralization is completed, deionized water is used for centrifugal washing and drying.

3. The method for preparing the biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer scraping and hot pressing molding process according to claim 1, characterized in that: The preparation of the HA-CNC / PLGA solution in step 2) is specifically as follows: first prepare a PLGA solution, the ratio of PGA to PLA in the PLGA molecule is 25:75-75:25, the molecular weight is 10000-100000, the concentration of PLGA is 15-25wt%, the solvent is one of N,N-dimethylacetamide, dichloromethane and chloroform, the dissolution process is heated to 80-90°C, stirred for 2-3h, 10-20wt% of HA-CNC is added to the PLGA solution, and after stirring, ultrasonic-assisted dispersion is performed for 30-60min, and the solution is allowed to stand for degassing.

4. The method for preparing the biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer scraping and hot pressing molding process according to claim 1, characterized in that: Step 2) During the layer-by-layer scraping process, the temperature of the hot stage is 50-60° C. A scraper is used to scrape the HA-CNC / PLGA solution layer by layer on the hot stage. After the solvent of the previous layer evaporates completely, the scraping is continued. The standard thickness is 6 mm-1.5 cm.

5. The method for preparing the biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer scraping and hot pressing molding process according to claim 1, characterized in that: In step 3), the mold is preheated to 80-120° C. During the hot pressing process, the hot pressing target temperature is 150-200° C., the pressure is 5-10 MPa, and the time is 30-180 s. After that, the compressive load is removed and the mold is naturally cooled and solidified.

6. The method for preparing the biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer scraping and hot pressing molding process according to claim 1, characterized in that: In step 3), the secondary shaping pressure is 5-6 MPa and the time is 5-10 min; During the dialysis process, deionized water was used for 12-24 hours, and the solution was changed every 2 hours; During the drying process, the drying temperature is 50-60°C and the drying time is 5-10h.

7. The method for preparing the biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer scraping and hot pressing molding process according to claim 1, characterized in that: In step 4), a hole structure array is formed by cutting on the sample, wherein the formed hole structure is a round hole or a square hole with a size of 400-600 μm, and adjacent hole structures are spaced 400-600 μm apart.

8. A biomineralized cellulose nanocrystal composite PLGA porous skull repair scaffold material based on layer-by-layer scraping and hot pressing molding process, characterized in that: The method is adopted as described in any one of claims 1 to 7.